Critical Success Factors of Agile Software Development - A Systematic Literature Review - Ojha, Trailokya Raj (SCITECH Nepal, 2023)
Agile software development has gained more popularity due to its capacity to manage constantly changing needs and generate high-quality software in less time. However, several success factors are required for an agile project to succeed. Agile development technique, delivery strategy, project team training, customer and staff involvement, management commitment, organizational culture, communication, and project management process are critical success factors (CSF) discovered in this study. This study's goal is to locate and evaluate these crucial elements of the agile software development methodology's success. A systematic literature review was conducted to study and analyze the previous studies to identify the CSFs in agile development. The findings of the literature review indicate that technical, people, organizational, and process factors are crucial for the success of agile projects. Each CSF falls into any one of these factors. Overall, this study's findings emphasize the significance of CSFs in the agile software development process. Organizations and software development teams can enhance their agile processes and raise the likelihood of project success by being aware of these aspects. Teams may create high-quality software in less time while simultaneously fulfilling the goals and expectations of the customer by concentrating on different success factors.